Pengaruh Digital Marketing dan Kualitas Pelayanan Terhadap Keputusan Pembelian Jasa Kreatif pada UMKM Desain Aja Dulu - Dede Crystien Panjaitan; Fransisca Herta Manik; Bobby Hartanto; Willy Cahyadi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to optimize digital marketing strategies and improve service quality in order to strengthen competitiveness and influence consumers' purchasing decisions. In creative service businesses, which are predominantly intangible, purchasing decisions are determined not only by effective digital marketing but also by the quality of services delivered to customers. This study aims to analyze the influence of digital marketing and service quality on purchasing decisions for creative services at Desain Aja Dulu MSME in Tebing Tinggi City. This research employed a quantitative approach using a causal explanatory design. The population consisted of 500 consumers, while 84 respondents were selected using the Slovin formula and purposive sampling technique. Primary data were collected through questionnaires using a five-point Likert scale, whereas secondary data were obtained from company documentation. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 3.0 software. The findings indicate that digital marketing has a positive and significant effect on purchasing decisions with a path coefficient of 0.407, a t-statistic of 3.042, and a p-value of 0.002. Service quality also has a positive and significant effect on purchasing decisions with a path coefficient of 0.447, a t-statistic of 3.244, and a p-value of 0.001. Furthermore, the R-Square value of 0.648 indicates that digital marketing and service quality jointly explain 64.8% of the variance in purchasing decisions, while the remaining 35.2% is explained by other variables outside the scope of this study. The study concludes that effective digital marketing supported by excellent service quality can significantly improve purchasing decisions in creative service MSMEs. These findings provide practical insights for MSME practitioners in developing digital marketing strategies and improving service quality to enhance business competitiveness.